Phytochemical Study and Isolation of Scopolutin from Pimpinella anisum Seeds Grown in Iraq - Noor Mohsen Nasser; Widad M K Al-ani; Zahraa A.E Al Naqqash (Indian Journal of Forensic Medicine & Toxicology, 2021)
As widely known plants are divided into many categories, one of them is the herbs; which have been alwaysused as effective remedies to treat many health issues. One of these remedies belongs to our plant understudy Pimpinella anisum (anise), which belongs to Umbelliferae family, that has been characterized as anaromatic plant used in traditional medicine as carminative, disinfectant, and galactagogue. Anise dry seedswere collected from Iraqi herbal market to investigate their chemical constituents by using two methods:one of them hydrodistillation method using Clevenger apparatus in which oil sample was collected and thenanalyzed by GC/MS and revealed the presence of anethol as the major constituent with percentage of 82.91% of the oil; the second method was alcoholic extraction by Soxhlet apparatus with ethanol till exhaustionthen the extract was concentrated by evaporation under vacuum, after that partition with ethyl acetate wasdone, the ethanol layer was discarded while the ethyl acetate layer was concentrated under vacuum, thecollected fraction were analyzed by TLC comparing it with standard Scopoletin .Phytochemical screeningproved that the plant contain Scopoletin and was confirmed by comparing Rf value of the sample with thestandard in three different solvent systems.